Kinetic Column Evaluation of Potential Construction Options for Lessening Solute Mobility in Backfill Aquifers in Restored Coal Mine Pits, Powder River Basin, USA - Jeff B. Langman; Julianna Martin (Hydrology)
Following open-pit coal mining in the Powder River Basin, landscape reconstruction includes the construction of backfill aquifers from overburden waste rock. With overburden disaggregation and the re-introduction of groundwater, the weathering of newly available mineral surfaces and mobilization of nanomaterials can impact groundwater quality even when such issues were not previously detected in the overburden’s groundwater. Kinetic columns of Powder River Basin waste rock were used to evaluate backfill construction options—zeolite amendment, and soil amendment, compaction, rinse—that could reduce potential groundwater quality impacts. The leachate from each column was collected twice weekly for 20 weeks. The Eh and pH of the leachate substantially varied during an initial high-weathering period indicative of the traditional weathering of newly exposed mineral surfaces and the weathering and flushing of mobile particles. Correspondingly, select elements, such as arsenic and cadmium, were present in relatively high concentrations during this initial weathering period. Waste rock that was compacted or rinsed produced leachate with less solutes and potential contaminants when compared to the unaltered and zeolite- and soil-amended waste rock. Greater compaction during backfilling is possible but may require additional consideration for connecting the surface drainage network to the surrounding area. Rinsing of the waste rock is a viable construction option because of the temporary storage of the waste rock prior to backfilling but would require leachate collection for contaminant treatment.